Occurrence of 'gang of five' Shiga toxin‐producing Escherichia coli serogroups on Belgian dairy cattle farms by overshoe sampling. (10th December 2020) - Engelen, F.; Thiry, D.; Devleesschauwer, B.; Mainil, J.; De Zutter, L.; Cox, E.
Abstract: Shiga toxin‐producing Escherichia coli (STEC) are foodborne pathogens responsible for global outbreaks. This study was conducted to investigate the occurrence of 'gang of five' STEC serogroups (O26, O103, O111, O145, O157) on Belgian dairy cattle farms by overshoe (OVS) sampling, and to evaluate the presence of virulence genes in the obtained isolates. A total of 88 OVS, collected from the pen beddings of 19 Belgian dairy cattle farms, were selectively enriched in mTSBn, followed by immunomagnetic separation and plating onto CT‐SMAC for O157 STEC isolation, as well as in Brila broth, followed by a selective acid treatment and plating onto CHROMagar TM STEC and chromID TM EHEC for non‐O157 STEC isolation. Overall, 11 of 19 farms (58%) tested positive for presence of 'gang of five' STEC. O26 STEC was most frequently isolated from OVS (11/88; 12·5%), followed by O157 (10/88; 11·5%), O145 (3/88; 3·5%) and O103 (3/88; 3·5%). Additionally, 35% of the OVS collected from pens housing young cattle 1–24 months of age tested positive for 'gang of five' STEC, indicating that this age category is more likely to harbour STEC compared to new‐born and adult cattle. Importantly, half of the obtained 'gang of five' STEC isolates (48%) possessed the eae and stx2 gene, suggesting a high pathogenic potential to humans. Abstract : Significance and Impact of the Study: Shiga toxin‐producing Escherichia coli (STEC) are important foodborne pathogens responsible for haemorrhagic colitis and haemolytic‐uremic syndrome. Cattle are the major natural reservoir and excrete these bacteria in their faeces. This study investigated the occurrence and pathogenic potential of 'gang of five' STEC (O26, O103, O111, O145, O157) on Belgian dairy cattle farms and implemented a practical and animal‐friendly sampling method aimed at promoting more widespread STEC surveillance in the bovine reservoir. Since these serogroups are most frequently implicated in human illness, more information on their presence in the bovine reservoir is required to develop efficient strategies aimed at reducing bovine carriage and the risk of human transmission.